The Successful Journey of a Diplomat and Negotiator Case Study of Mrs. Retno Marsudi - Tri Wulandari; Kalina Alya; Disha Yori Farhana; Yusawinur Barella (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article takes an in-depth look at Ms. Retno Marsudi's successful career in diplomacy, as well as the factors that played a role in this achievement, while providing concrete examples of the practice of diplomacy. Using a descriptive research methodology, it explores theories of global diplomacy and the practice of Indonesian diplomacy. The research findings confirm the central role played by Ms. Retno Marsudi in building Indonesia's diplomatic relations with other countries. She is known for her strong leadership, communication skills, and wisdom in handling sensitive issues. In addition, this article also illustrates how Indonesia's free and active foreign policy is realized through effective diplomatic efforts, especially in achieving peace between Palestine and Israel. In the global context, Ms. Retno Marsudi's diplomatic work reflects Indonesia's commitment to play an active role in fighting for international peace and justice. In conclusion, Ms. Retno Marsudi's career journey not only provides inspiration, but also provides valuable lessons in the practice of diplomacy that has a positive impact globally.